Coupled Néel domain wall motion in sandwiched perpendicular magnetic anisotropy nanowires - Purnama, Indra (2015)
The operating performance of a domain wall-based magnetic device relies on the controlled motion of the domain walls within the ferromagnetic nanowires. Here, we report on the dynamics of coupled Néel domain wall in perpendicular magnetic anisotropy (PMA) nanowires via micromagnetic simulations. The coupled Néel domain wall is obtained in a sandwich structure, where two PMA nanowires that are separated by an insulating layer are stacked vertically. Under the application of high current density, we found that the Walker breakdown phenomenon is suppressed in the sandwich structure. Consequently, the coupled Néel domain wall of the sandwich structure is able to move faster as compared to individual domain walls in a single PMA nanowire.